Menu card for a dinner given by the Irish Republican Delegation in London - Duggan, Éamonn, 1874-1936 (1921)
Menu card belonging to Éamonn Duggan, who was a member of the Irish Republican Delegation in London throughout the Anglo-Irish Treaty negotiations.
Keywords: Anglo-Irish Treaty -- (1921 December 6)